Formulasi Gel Pengelupas Sel Kulit Mati yang Mengandung Sari Buah Nanas (Ananas comosus L) antara 17 sampai 78% - TETI INDRAWATI; FINA ZISSAKINA (JURNAL ILMU KEFARMASIAN INDONESIA, 2011)
The juice of Ananas comosus L. contains bromelain which has been known to defoliate dead skin cells. Investigation on five gel formulations containing 17%, 33%, 50%, 67% and 78% of the juice of Ananas comosus L with 4% of HPMC as gelling agent, have been carried out. The stability of all formula were examined by the accelerated test method at room temperature and 40 oC for 6 weeks. Parameters observed were organoleptic, homogeneity, syneresis, viscosity, flow behavior, spreading ability, and pH. Results indicated that the higher the juice concentration in the gel would reduce the gel stability progressively. Gel formula using 4% of HPMC containing 17% or 33% of Ananas comosus juice can be produced while maintaining good physical stability for 6 weeks. The products were pale yellow to yellow in color, homogeneous, and have viscosity of 13000-45800 cps, pH 4.0-4.9, pseudo plastic flow, and spreading ability of 2732.58 to 4534.16 mm².